Peran L’oréal dalam Responsible Mica Initiative: Pengentasan Eksploitasi Pekerja Anak pada Pertambangan Mika di India - Ni Komang, Budiayu; Sushanti, Sukma; Nugraha, A.A Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 1 (2023): JURNAL DIKSHI, 2023)
This study aims to examine the role of L’Oréal in the Responsible Mica Initiative related to eradicating the exploitation of child labor in India's mica mines using qualitative methods. Child labor is a very complex issue in India's mica industry. L’Oréal as a multinational company who source mica in India takes a role through the Responsible Mica Initiative (RMI) to address issues related to child labour. The author uses the conceptual framework of child labor, multinational companies in the global political economy and corporate social responsibility (CSR) to see the role of L’Oréal in eradicating the issue of exploitation of child labor in India’s mica mines. This research can then see the role of L’Oréal through the Responsible Mica Initiative (RMI) in mapping the company's supply chain and standardizing the workplace, empowering communities and assisting the establishment of a comprehensive legal framework in the states of Jharkhand and Bihar.